A Machine Learning Algorithm for Identifying Atopic Dermatitis in Adults from Electronic Health Records - Gustafson, Erin (Proc (IEEE Int Conf Healthc Inform), 2017)
The current work aims to identify patients with atopic dermatitis for inclusion in genome-wide association studies (GWAS). Here we describe a machine learning-based phenotype algorithm. Using the electronic health record (EHR), we combined coded information with information extracted from encounter notes as features in a lasso logistic regression. Our algorithm achieves high positive predictive value (PPV) and sensitivity, improving on previous algorithms with low sensitivity. These results demonstrate the utility of natural language processing (NLP) and machine learning for EHR-based phenotyping.